ﻟﻜِﺒْﺮُ واﻟﺨﺸﻮع ﻓﻲ اﻟﻘﺮآن اﻟﻜﺮﯾﻢ‬ ‫)دراﺳﺔ ﺗﺤﻠﯿﻠﯿ - أ.حميدة صالح البلداوي (College of Education for Women, 2019)
Abstract What the research come to: 1- The presentation of the image of the proud person in this mortal life appeared in several styles such as (conversation) arousing the insert once and convincing in other time, (confirmation) in all its types، (argument) scolding with the gradual progress of time of the discourse .Interview and parallelism are two of these styles with the presences of the repetition style especially in the topics that has a reference to the theme of (pride) being implied not directly stated. The Koran discourse varied in its reference to the theme of pride according to the context which is mentioned directly (eighteen times) which formed one third of the number of times of its mentioning in the Holy Koran and in different forms. 2- The verb with additional letters is repeated (‫ﺘﻜﺒﺮ‬Ǵ‫ ﯾﺴ‬-‫ﺘﻜﺒﺮ‬Ǵ‫ )اﺳ‬and the present participle that is derived from the verb more than others giving the sense of the request and "he becoming" and the sense of how great the guilt which the request left in the person's self. 3- The verbs mentioned more than the nouns referring that this urgent adjective is not natural creatures and changeable not adherent, yet what is constant is modesty, and because the verb is variable and changeable the call was repeated to dismiss to renounce pride and be back to the origins. Pride is also mentioned in the form of present participle referring to the event either described with atheism or arrogant or in the sense of him being chained with his insistence that is because the present principle is not in the reality of perception but not in the order of Allah (be raised far above) in the changing and variable form for the future. The moral evidence to understand the meaning of the event comes from the side of the meaning attributed to the additional letters of the forms and what the form (‫ﺘﻔﻌﻞ‬Ǵ‫ )اﺳ‬serve as request, power, and fault, also what the form (‫ﻞ‬Ǵ‫)ﺗﻔﻌ‬include of artificiality and exposition to the reverence which appears in the Koran discourse in the form of adverb, describing the manner and restricting the verb, with the variety of types and subjects, leading to the assertion in its repletion overlapping and the sequence of its sentences. This proves the faith in "right" and calmness of the "self" in the believers, opposite it with the sense in the unbelievers like lowness and disgrace. The image of reverence comes perfectly to include the calmness of the heart and self organs and the entire creatures which is the reverence caused by faith in any doctrine and in any situation with desire and fear in this mortal and in the ever after that is because the mortal evidence or one which shape the form.